Pengaruh Variasi NaOH Pada Polimerasi Kuersetin Terhadap Efisiensi DSSC - Hijri, Fadhillah; Hardeli, Hardeli (Periodic, 2023)
Dye-sensitive solar cells are third-generation solar cells that convert photon energy into electrical energy. DSC solar cells use dyes to increase efficiency. The dye used is polymerized first to increase the amount of π -π* so that more photons are absorbed and efficiency increases. The dye used in this research is quercetin which is polymerized with a glutaraldehyde crosslinking agent. Quercetin polymerization can be influenced by several factors, one of which is NaOH which acts as an initiator. NaOH plays a role in opening the epoxy ring so that the polymer chain gets longer. ITO glass is coated with TiO2 electrodeposited with ZnO. The results of the measurement of the highest efficiency were found in the 1% NaOH of 8.33% with a density of 0.52 g/cm3 and a degree of polymerization of 3.05